A word from our Editor-in-Chief - Mihail Aurel Titu; Mihai Dragomir (Nonconventional Technologies Review)
The community of researchers in the field of nonconventional technologies and related topics is now in between the fondly remembered 2024 ICNcT Conference in Bucharest and the exciting upcoming 2025 ICNcT Conference in Timișoara. As papers from 2024 are still being published, the Nonconventional Technologies Review maintains its commitment to high quality research that can contribute to the overall competitiveness and innovativeness of the manufacturing sector in Romania and internationally. The four issues to be published this year represent a showcase of the preoccupations, capabilities and results obtained in the area of manufacturing technologies, while also integrating emerging technologies such as artificial intelligence, digital twins and additive manufacturing. A special mention should be given to the AI solutions that are developing extremely fast and have the capability to infuse all sectors, including our own, with a new wave of creativity and original problem-solving approaches under conditions of extreme performance with respect to time and necessary means.